The Status of Hand Arrest Operations in the View of Legal Practitioners - Hasan, Faradila; Makka, Misbahul Munir (Kawanua International Journal of Multicultural Studies, 2023)
This article intends to know the status of the Hand Arrest Operation (OTT) carried out by the Corruption Eradication Commission (KPK) according to the views of legal practitioners. With a normative approach, this study examines the problems legal practitioners face more deeply. There is a difference between Hand-Arrest and Arrested Operations. It means that Hand Arrest Operations (OTT) and Being Arrested (TT) are the same if the procedure follows the rules set, namely Article 18 of the Criminal Code. It is in line with the views of practitioners of law.